Express Synthesis of YAG:Ce Ceramics in the High-Energy Electrons Flow Field - Lisitsyn V. M. Viktor Mikhailovich; Tulegenova A. T. Aida Tulegenkyzy; Kaneva E. V. Ekaterina Vladimirovna; Musakhanov D. A. Dosymkhan Abitkhanovich; Gricenko (Gritsenko) B. P. Boris Petrovich (2023, 2023)
Title screen